Sistem Informasi Pemesanan “Cangkrukan Cak Suga”Berbasis Web - Nuzul Hikmah; Misdiyanto Misdiyanto; Tyas Agustian Mahardika (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
Coffee is one of the agricultural commodities that plays a vital role as a refreshing beverage and is categorized as a perennial crop. Currently, coffee is becoming a trend and an integral part of people's lifestyles. Coffee is divided into two main varieties: robusta and arabica, each with its distinct characteristics. Differentiating between robusta and arabica coffee beans can be challenging due to their similar physical appearance. Deep learning-based smart engines can offer a solution to this problem, although their complex user interfaces often hinder accessibility. To address this issue, a Spiral development method was employed to build an application using PHP programming language and Codeigniter 4 framework. This application facilitates easy detection of coffee bean types through both a website and a RESTful API, allowing users to access it online from any device. The application underwent comprehensive black box testing, demonstrating successful functionality aligned with the initial design objectives. It is expected that this application will solve the identified problem and provide significant assistance to coffee enthusiasts and the general public in easily distinguishing between various coffee bean types. Users can effortlessly recognize and differentiate between different coffee beans while obtaining useful information about their preferred coffee beans.